Cultivating Eco-Faith Literacy: Challenges in Aligning Vocational English Curriculum with Sustainable Religious Tourism Needs - Imam Wahyudi Karimullah; Saiful Marhaban; M Galuh Elga Romadhon (Jurnal Pendidikan Progresif, 2026)
This study aims to investigate how English teaching in Indonesian vocational high schools, particularly within tourism-related programs, contributes to the development of communicative, ethical, and sustainability-oriented competencies required in the emerging field of religious tourism. Beyond merely identifying implementation gaps, the study seeks to clarify the conceptual alignment among the Merdeka Curriculum, English for Specific Purposes (ESP), and the growing demand for eco-religious tourism literacy. The research addresses an underexplored area in ESP studies: the integration of sustainability in religious tourism into vocational English education. Using a phenomenological-interpretivist approach, this qualitative study draws on semi-structured observations conducted in English classrooms within tourism departments at vocational high schools in East Java. Data were analyzed inductively to explore teachers’ pedagogical interpretations, classroom practices, and the contextual factors shaping curriculum enactment. The implementation of vocational English teaching remains limited despite the curriculum’s emphasis on autonomy and innovation. Teachers’ interpretations of curricular flexibility varied widely, leading to inconsistent pedagogical strategies. Some teachers independently integrated project-based learning simulations that embed religious values, environmental sustainability, and local cultural identity, yet such practices were not institutionalized. Furthermore, insufficient professional development, lack of ESP-oriented resources, and limited institutional support hindered systematic alignment between English instruction and the competencies needed in religious tourism contexts. The study contributes conceptually by demonstrating that under implementation is not merely a technical issue but reflects broader challenges of curriculum interpretation, teacher capacity, and contextual responsiveness. It highlights a significant gap in the existing ESP literature regarding sustainability-driven, value-based tourism communication skills. These insights underscore the need for developing structured ESP modules tailored to religious tourism and eco-tourism, supporting vocational schools in aligning English instruction with emerging industry demands. Keywords: ESP, sustainable tourism, vocational high school, merdeka curriculum, religious tourism.